PENGEMBANGAN MODEL FUZZY MULTIPLE ATTRIBUTE DECISION MAKING (FMADM) UNTUK PENGELOLAAN LOWONGAN KERJA - Muhammad Ichsan; Rahmad Syah; Muhammad Iqbal (TECHSI - Jurnal Teknik Informatika, 2014)
A lot of decision-making problems encountered in various fields of work, such as the recipient's eligibility status field of the provision of bank credit, scholarships and recruitment in the company. Most of these problems aim to select a set of alternatives based on multiple attributes (criteria). The method is often used to resolve such issues is Fuzzy Multiple Attribute Decision Making (FMADM). Thesis is appointed a case of acceptance of a new employee in a company using a weighted fuzzy logic Simple Additive Weighting (SAW) in finding a weight value of each attribute. Search theweights is done through a subjective approach. The study was conducted bysearching bobt value for each attribute, and then carried out the ranking process that will determine the optimal alternative, the best warehouse location.